Design and Implementation of Internet of Things for Land Information System - Lasisi, J. O.; Nwokenkwo, C. B.; Mohammed, J. K. (International Journal of Real Estate, 2026)
Technological advancement has spread across all sectors, including the built environment, and has gradually been embraced in the real estate sector. The Internet of Things (IoT) is considered one of the most important emerging technologies for real estate professionals. However, the potential of IoT applications in real estate practice has yet to be fully explored, particularly in land administration. Although the Land Information System (LIS) has gained serious attention, one of the major challenges it has not fully addressed is the alteration of cadastral layouts and the protection of boundary beacons. It became imperative to deploy IoT technology to strengthen the LIS and safeguard land property rights. This study designed and implemented an IoT-based system for the Land Information System in Bida, Niger State, Nigeria. Information was gathered through a reconnaissance survey of the Federal Polytechnic Bida campus, review of existing cadastral plans, and assessment of current LIS applications. A physical prototype was developed using an ESP32 microcontroller, NEO-6M GPS module, and 0.96-inch OLED display. The smart beacon continuously monitors its GPS coordinates. Once a reference location is stored, any movement triggers an immediate “Damage Detected!!!” or “ALERT! Location Changed!!!” notification. The system sends the alert via a WhatsApp bot using the CallMeBot API with a direct Google Maps link containing the new latitude and longitude. Field testing on the polytechnic campus confirmed that the system delivered accurate real-time location tracking, reliable tamper detection, and instant notifications compared with traditional manual beacon inspection; the IoT solution eliminated the need for frequent physical visits, reduced response time to alterations, and provided verifiable evidence through live map links. The study therefore provided a practical, low-cost IoT-based LIS that adds value to existing land information systems and contributes to the literature by demonstrating how IoT can be implemented for beacon management in cadastral layouts to achieve sustainable land administration in Nigeria.
Keywords: Design; Implementation; Internet of Things; Land Information System; Smart beacon